Análise da condição bucal, sistêmica e sociodemográfica das pessoas com Diabetes Mellitus tipo II e conhecimentos sobre a doença - Batista, Ana Cristina Beviláqua (2013)
This study is about a documental, transversal exploratory research of quantitative approach, performed in the city of Sobral, Ce. Were analyzed the oral health conditions, systemic and sociodemographic of patients with Diabetes Mellitus type II registered in the Basic-Health Units of this city, as well evaluated the patients' knowledge level about the disease and its relation with oral health. The sample was consisted of 422 patients with Type 2 DM, who participated voluntarily in the study. The patients were evaluated through an application of an instrument that approached sociodemographic data; the systemic evaluation, oral, diabetes knowledge questionnaire DKN - A and knowledge about oral health/diabetes. The sociodemographic factors analyzed were: sex, age, marital status, educational level, employability and income. The oral health status evaluated edentulism, the presence of oral lesions and DMFT. The systemic condition included BMI analysis, capillary blood glucose, blood pressure, progression of the disease, abdominal circumference and drug therapy. The results showed that 77,3% of the evaluated ones were women, 76,1% had minimal age of 51 years, 61,85% were married and had low schooling. About 72,28% of the individuals were overweight and obese, 61,18% of the evaluated ones had hypertension associated to type 2 DM. Regarding capillary blood glucose, 54,9% of the interviewees showed capillary blood glucose above 201 mg/dl. In assessing the oral health conditions, 91% of the interviewees presented partially or totally edentulous and only 2,37% were patients with oral lesions. For the DMFT the average found was 27,51% in the age between 60 and 70 years. Regarding the assessment of knowledge about diabetes, 61,61% of the sample abtained scores equal or inferior to 6, indicating unsatisfactory results for knowledge and comprehension of the disease's management. About knowledge of oral health and diabetes, stands out 64,46% of the interviewees had been taught about oral health and of these, 47,63% the source of information was the dental surgeon. Referring to the relation between type 2 DM and oral health, 51,90% of the sample said to be unrelated and 53,08% believed that DM couldn't harm in their oral health condition. Lastly, 82,26% of the patients informed to never had received any information about the relation between oral health and diabetes. The interest to measure the user's knowledge about the DM consequences concerning oral health, emerged from the oral findings found in dental clinic in patients metabolically decompensate. With this, we agreed with some authors who talk about the importance in the use of instruments or questionnaires which make available the knowledge of diabetic patients facing the disease and its probable oral repercussions. These instruments allows measuring of this knowledge and this enables the better planning of the directed therapy for each case, to elaborate teaching activities and health educational practices, aimed to DM patients and their needs, preventing grievance. Moreover, enables the prevention of complications by managing the disease and their oral health condition, providing the diabetic patient an improvement in their entire health.